STUDIES ON THE PREVALENCE OF GASTRO-INTESTINAL NEMATODES IN RUMINANT ANIMALS SLAUGHTERED IN BIU LOCAL GOVERNMENT ABATTOIRS, BORNO STATE, NIGERIA - Alhaji Mohammed, Usman; Fidelis, A. V.; Victor, J. G. (FUDMA JOURNAL OF SCIENCES, 2023)
An epidemiological study was conducted from September-November, 2022 on the prevalence of gastrointestinal nematodes species among naturally infected ruminants slaughtered in Biu Local Area of Borno state, using centrifugal flotation techniques. Out of three hundred and eighty four (384) ruminants (162 goats, 110 sheep and 112 cattle) examined in the three selected abattoirs (Biu, Maringa and Buratai), 239 (62.34%) were infected. Maringa had the prevalence rate of 64.65%, Biu 63.89% and Buratai 63.16%. Although the highest faecal egg counts was recorded in Cattle 66.07%, the difference in prevalence rate between the different location and species of the animal were statistically insignificant p<0.05. The parasites identified were Ascaris lumbricoides 33.81%, Ancylostomidae spp 30.93%, Trichosrongylus spp 16.54%, Strongyloides stecoralis 11.27%, Haemonchus contortus 5.51%, and Entoribius vermicularis 1.91%. Fulani cattle breed had the prevalence rate of 20 (71.43%), Wad Sheep 45 (66.18%) and West African Dwarf goat 80 (65.57%). The difference in prevalence rate between the different breed of all the animals were not statistically significant p<0.05.The prevalence rate was 47 (72.31%) in male goats, 20 (41.67%) sheep and cattle 31 (67.39%) whereas female counterparts had 50 (51.55%), 48 (77.41%) and 43 (65.15%) in goat, sheep and cattle respectively. Both young and adults were infected with GI nematodes. Gastrointestinal nematodes are endemic in the study area. Therefore, mass administration of anthelmintic drugs, regular vaccination as well as educating the livestock’s farmers toward insuring production of healthy meat and improvement of their welfare is required to control the parasite in the study areas.